2020
DOI: 10.3390/nano10030435
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Magnetic Entropy Change and Relative Cooling Power in La0.7Ca0.23Sr0.07MnO3 Electrospun Nanofibers

Abstract: We present experimental evidence about the magnetocaloric tuning effect in one-dimensional nanostructure fibers mixed-valence manganite as synthesized by electrospinning techniques and under heat treatments of 973, 1073 and 1173 K. The stoichiometry obtained is La0.7Ca0.23Sr0.07MnO3 and Rietveld refinement indicates a single-phase with an orthorhombic (Pnma) crystal structure. Scanning and transmission electron microscopy observations indicate coalescence in granular colonies of La0.7Ca0.23Sr0.07MnO3 nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…decrease in strength of M B . It resulted in a reduction in the net magnetization of the spinel ferrite nanofiber at 300 K. Similar results have been reported by other research groups [4,28]. Moreover, the reduction in the saturation magnetization (Ms) and coercivity (Hc) following the addition of aluminium (Al) content can be ascribed to the characteristics of the surface of the synthesized Al-substituted CFO nanofiber.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…decrease in strength of M B . It resulted in a reduction in the net magnetization of the spinel ferrite nanofiber at 300 K. Similar results have been reported by other research groups [4,28]. Moreover, the reduction in the saturation magnetization (Ms) and coercivity (Hc) following the addition of aluminium (Al) content can be ascribed to the characteristics of the surface of the synthesized Al-substituted CFO nanofiber.…”
Section: Resultssupporting
confidence: 87%
“…These findings are consistent with similar results reported by other research groups. [28,29]. Elemental analysis of the samples has been investigated using EDAX analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These methods include different combinations of precipitation and impregnation of copper-and zinc-oxides over ZSM-5, which enable the establishment of different levels of distribution of the active materials for catalytic CO 2 hydrogenation to methanol and its dehydration to DME. It has been demonstrated that the electrospinning (ES) technique is an efficient technique to produce fibers to be used in a wide range of applications such as the catalysis [22], electro-and photocatalysis [23,24], membranes [25], biomedicine [26], and magnetic refrigeration [27]. In this context, ES catalysts in the form of fibers were tested in this research along with the catalysts synthesized using the above-mentioned methods.…”
Section: Introductionmentioning
confidence: 99%